El «Apologético de las comedias españolas» a nueva luz - Muriel Elvira (Criticón, 2015)
This article sets Ricardo de Turia’s «Apologético de las comedias españolas» in the tradition of Spanish texts that rework arguments and examples taken from the polemic surrounding Il Pastor Fido, in order to defend or attack the Spanish Comedia Nueva. It analyses how the «Apologético» relates to other earlier Spanish texts using the same Italian sources with the same aim: the Arte Nuevo de hacer comedias by Lope de Vega, chapter XXI of the Didascalia multiplex by Francisco Fernández de Córdoba and the Plaza universal de todas ciencias y artes by Cristóbal Suárez de Figueroa. The article also studies the way in which Guarini’s ideas are assimilates in Spain, as they are used to defend a legitimate break from traditional poetic rules, even pushing beyond Guarini’s strict adhesion to Aristotle.